198k views
1 vote
11-(3x+1) = 7(x-6)+2

2 Answers

3 votes

Answer:

11-3x-1=7x-42+2

Put all like terms together

10+40=10x

x=50

User Deividy
by
5.2k points
6 votes

Hello!


\large\boxed{x = 5}

11 - (3x + 1) = 7(x - 6) + 2

Distribute the coefficients outside of the parenthesis:

11 - (3x) - (1) = 7(x) + 7(-6) + 2

Simplify:

11 - 3x - 1 = 7x - 42 + 2

Combine like terms:

10 - 3x = 7x - 40

Add 3x to both sides to isolate x:

10 = 10x - 40

Add 40 to both sides:

50 = 10x

Divide both sides by 10:

x = 5

User Vlad Halmer
by
5.4k points